The Indirect Fiscal Benefits of Low-Skilled Immigration - Mark Colas; Dominik Sachs (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Low-skilled immigrants indirectly affect public finances through their effect on native wages & labor supply. We operationalize this general-equilibrium effect in the workhorse labor market model with heterogeneous workers and intensive and extensive labor supply margins. We derive a closed-form expression for this effect in terms of estimable statistics. We extend the analysis to various alternative specifications of the labor market and production that have been emphasized in the immigration literature. Empirical quantifications for the U.S. reveal that the indirect fiscal benefit of one low-skilled immigrant lies between 770 and 2,100 annually. The indirect fiscal benefit may outweigh the negative direct fiscal effect that has previously been documented. This challenges the perception of low-skilled immigration as a fiscal burden.
Keywords: H20; J31; J62; J68; 330; immigration; fiscal impact; general equilibrium